Relações entre prática docente e competência linguístico-comunicativa: a perspectiva dos próprios professores - Padilha, Emanuele Coimbra (2015)
This work aimed at investigating the relations between teaching practice and Language-communicative competence of Spanish Foreign Language teachers from the public school, through the inference of their beliefs. Therefore, we identified the beliefs about linguistic and communicative competence of teachers and, as a result, these beliefs were related to their performance reported by the participants themselves in the classroom. The participants of this study were two Spanish teachers, working in public schools in Santa Maria city, who performed the initial training in Letters-Spanish graduation at the Federal University of Santa Maria. The methodology used was a qualitative study of case, based on metacognitive approach beliefs research (BARCELOS, 2001). We applied a questionnaire to answer the main purpose. Secondly, a semi-structured interview was made. The results showed that these teachers believe Linguistic competence communicative is characterized by complementarity of linguistic and communicative component. This division into two components still carries a structuralist notion that considers the linguistic part precedes and prevails on the communications components and also that this is a belief that may have been caused by the influence of the nomenclature linguistic and communicative competence, by Almeida Filho (1993), adopted in this study. In relation to teaching practice reported by the teachers, it was found that the beliefs presented by the participants directly influence on performance. Thus, we concluded that the insufficient linguistic and communicative competence of the teacher leads to severe limitations in educational performance in relation to the oral performance.